A Note on the Biocidal Efficacy of Agave Extract on Bamboos - Lepcha, S. T. S.; Kumar, Satish (Indian Forester, 2008)
Results of preliminary tests on efficacy of Agave spp. locally called 'Rambans' extract against bamboo inhabiting moulds, borers and termites are reported. Agave extract has been found to resist termite and borer attack in bamboo, but has been found ineffective in preventing growth of mould fungi.